IMPROVING AIR QUALITY IN THE CLASSROOM THROUGH THE AIR CONDITIONING CLEANING PROGRAM AS AN EFFORT TO MAINTAIN STUDENT HEALTH IN THE LEARNING PROCESS AT THE ANNUR SIDOARJO ISLAMIC BOARDING SCHOOL - Wisaksono, Arief; Purwanti, Yanik (Antis-publisher, 2025)
Objective: A clean, tidy classroom with adequate lighting and a cool, stable temperature will encourage students to focus and feel comfortable during the learning process. Room temperatures that are too hot or too cold can disrupt concentration, cause drowsiness, and even cause physical discomfort, which ultimately reduces learning effectiveness. Managing room temperature through good ventilation or optimal use of air conditioning is important. Additionally, a pleasant classroom environment—characterized by positive teacher-student relationships, the use of interactive learning methods, and a supportive emotional atmosphere—is essential. Method: The Waterfall Method is one of the linear and sequential methods used in system or project development. This method includes the initial observation and coordination stage, scheduling of AC cleaning activities, AC cleaning implementation, counseling and education, monitoring and evaluation, which must be completed before proceeding to the next stage, like a waterfall. Results: The classroom AC cleaning program has proven to have a positive impact on air quality and the comfort of the teaching and learning process. Comprehensive AC unit cleaning successfully reduced dust and dirt that could potentially harm the health of students and teachers. Novelty: Observations and questionnaires showed an increase in learning comfort and awareness of the importance of regular AC maintenance. The educational activities conducted also successfully fostered knowledge and awareness among teachers, staff, and students about the importance of maintaining a clean learning environment. This program is expected to serve as the first step in establishing a culture of regular school facility maintenance as a preventive measure to safeguard the health of school community members.